Ab-initio calculations and ellipsometry measurements of the optical properties of the layered semiconductor In4Se3 - Makinistian, Leonardo (2010)
In this work, we present a thorough study of the optical properties of the layered orthorhombic compoundIn4Se3. The dielectric function—real and imaginary parts, the complex refraction index, the reflectivity, theabsorption coefficient, and the conductivity of In4Se3 were calculated with the inclusion of the spin-orbitinteraction, using an ab initio FP-LAPW method based on DFT. Also, generalized ellipsometry was employedfor more precise measurement of the anisotropic dielectric functions for polarization along crystal a, b, and caxes of orthorhombic absorbing In4Se3 single crystals cut approximately parallel to (100) at photon energiesfrom 0.76 to 3.1 eV. Our experimental results show a good agreement with our calculations. We discuss thelocation and nature of the main optical peaks appearing in the spectra. The obtained optical functions displaya rather anisotropic behavior, mainly in the infrared-visible region. Our results seem to be predictive to a highextension, given the scarce experimental information about its optical properties.